2016
DOI: 10.1007/s13726-016-0446-4
|View full text |Cite
|
Sign up to set email alerts
|

Polycarboxylate superplasticizers of acrylic acid–isobutylene polyethylene glycol copolymers: monomer reactivity ratios, copolymerization behavior and performance

Abstract: such as dependence of the mole fractions in the copolymer on the mole fractions of unreacted monomers in solution, variation of copolymer compositions with conversion and sequence length distribution. The fluidity and flow loss of pastes containing PCEs were investigated, and the appropriate PCEs dosages resulted in a better workability of cement pastes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…So, we concluded that IPEG2400 showed higher copolymerization activity with acrylic acid than HPEG2400. According to the former work of our research team, the testing reactivity ratio of acrylic acid and IPEG2400 are r AA = 1.131 and r IPEG = 0.042 . The testing reactivity ratio of acrylic acid and HPEG2400 is r AA = 1.54 and r HPEG = 0 .…”
Section: Resultsmentioning
confidence: 95%
“…So, we concluded that IPEG2400 showed higher copolymerization activity with acrylic acid than HPEG2400. According to the former work of our research team, the testing reactivity ratio of acrylic acid and IPEG2400 are r AA = 1.131 and r IPEG = 0.042 . The testing reactivity ratio of acrylic acid and HPEG2400 is r AA = 1.54 and r HPEG = 0 .…”
Section: Resultsmentioning
confidence: 95%
“…According to the monomer reactivity rate, the relationship between copolymer composition and conversion rate is analyzed in the reaction systems. The specific calculation is shown in eq . ,, C = M 0 M M 0 = 1 M M 0 = 1 true( f 1 f 1 0 true) ϕ true( f 2 f 2 0 true) β true( f 1 0 δ f 1 δ true) γ where is ϕ = r 2 1 r 2 , β = r 1 1 r 1 , δ = 1 r 2 1 r 2 r 2 , γ = 1 r 1 r 2 false( 1 r 1 false) false( 1 r 2 false) ...…”
Section: Resultsmentioning
confidence: 99%
“…The specific calculation is shown in eq 9. 28,52,53 = = = i k j j j j j j y { z z z z z z i k j j j j j j y { z z z z z z i k j j j j j j y…”
Section: Compressive Strength Of Concretementioning
confidence: 99%
“…This makes these macromonomers notably less reactive, being kinetically more similar to vinyl ethers . In copolymerization reactions with acrylic acid and methacrylic acid, a major difference in reactivity ratios has been observed, making it difficult to produce homogeneous copolymer chains. , …”
Section: Introductionmentioning
confidence: 99%
“…Open literature about the reactivity ratios of these types of macromonomers is very scarce. In fact, the results are limited to a couple of sources available. ,, So far, three of these macromonomers have been studied together with acrylic acid. These are polyethylene glycol monovinyl ether (EPEG), polyethylene glycol 3-methyl-3-butenyl ether (IPEG), and polyethylene glycol 2-methyl-2-propenyl ether (HPEG).…”
Section: Introductionmentioning
confidence: 99%